Methanol Extract Alstonia scholaris L. R. Br as Hepatoprotective Mice (Mus musculus) Infected with Plasmodium berghei ANKA Strains - Martha Kaihena; Maria Nindatu; Abdul Mahid Ukratalo (Postgraduate, University of Mataram, 2023)
Alstonia scholaris L. R. Br is one of the traditional plants that contain natural antioxidant compounds which are thought to be able to repair damage to the liver cells of mice (Mus musculus) infected with Plasmodium berghei strain ANKA. This study aimed to determine the effect of methanol extract of Alstonia scholaris L. R. Br stem bark on levels of SGPT enzymes and liver cells of mice (Mus musculus) infected with Plasmodium berghei strain ANKA.Â Mice with a body weight of 20-30 g were infected with Plasmodium berghei as much as 0.1 ml per head and left until the percentage of parasitemia reached 1-5%. Then mice (Mus musculus) were given methanol extract of Alstonia scholaris L. R. Br stem bark at doses of 1, 10, 100, and 200 mg/kg BW for 4 consecutive days. After that, surgery was performed to take blood to observe SGPT enzyme levels and mice liver cells to be prepared with Hematoxylin Eosin (HE) staining. The results of ANOVA showed that the methanol extract of Alstonia scholaris L. R. Br stems bark doses of 1 mg/kg BW, 10 mg/kg BW, 100 mg/kg BW and 200 mg/kg BW could reduce SGPT enzyme levels and repair damage to the liver cells of mice infected with Plasmodium berghei ANKA strains